Management of GA3 application to enhance seed production in the CMS parent of rice (Oryza sativa) hybrids - JOSE, SOUMIA; CHAKRABARTY, S K; SHARMA, S P; DADLANI, M (The Indian Journal of Agricultural Sciences, 2011)
A field experimentwas undertaken to study the efficacy of split application of gibberell’ic acid (GA3) for foundation seed production of cytoplasmic male sterile line of rice. The results indicated a favorable role of GA3@90g1 ha and 180 gl ha with or without boric acid (1%) applied in 3 split doses in the.ratio of 1:2: 1 on alternate days starting at 5% panicle emergence stage were found nlost suitable for higher panicle exsertion, percent productive tillers and seed seed. An average seed yield ofabout 2.4 tonnesl ha was obtained using GA3@ 180 g/ha with three spit applications as compared to about 2 tonnesl ha with the existing recommendations. Thus a simple modification in application of GA3 at the panicle emergence stage was found to enhance seed production of CMS line of rice further.